Local Wisdom and Islamic Economics: Warung Madura MSME Success Strategy (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, including Warung Madura MSMEs. This research aims to analyze the development strategy of Warung Madura MSMEs from an Islamic economic perspective. This research uses a qualitative approach. Data collection techniques through in-depth interviews with Warung Madura owners and economic observers. A literature study was also carried out to explore the concept of Islamic economics and its application in developing MSMEs. The results of the research show that Warung Madura's MSME development strategy from an Islamic economic perspective offers a holistic and sustainable approach. By applying the principles of justice, sustainability, business ethics, human resource development and access to appropriate financing, Warung Madura can increase its competitiveness and contribute more to the local economy. It is hoped that this research can provide insight for stakeholders in formulating more effective MSME development policies and programs